Selective mitochondrial Ca2+ uptake deficit in disease endstage vulnerable motoneurons of the SOD1G93A mouse model of amyotrophic lateral sclerosis. (12th March 2013) - Fuchs, Andrea; Kutterer, Sylvie; Mühling, Tobias; Duda, Johanna; Schütz, Burkhard; Liss, Birgit; Keller, Bernhard U.; Roeper, Jochen
Key points: So far, increased excitability and calcium handling problems have been discussed as causes for motoneuron death in amyotrophic lateral sclerosis (ALS) mainly on the basis of studies in juvenile presymptomatic mice. We developed a brainstem preparation to analyse excitability and calcium handling during disease progression up to disease endstage of motoneurons in an ALS mouse model. Increased excitability of motoneurons is not seen at disease endstage, challenging this factor as a direct cause for motoneuron death in ALS. We show that calcium handling is remodelled during disease progression from mitochondrial uptake to mitochondrial uptake failure and increased plasma membrane extrusion, providing a compensatory mechanism that fails at disease endstage and might lead to a toxic calcium overload of the cells. Supporting this newly described compensatory endeavour of the motoneurons might be a promising therapeutic strategy. Abstract Amyotrophic lateral sclerosis is a progressive neurodegenerative disease that targets some somatic motoneuron populations, while others, e.g. those of the oculomotor system, are spared. The pathophysiological basis of this pattern of differential vulnerability, which is preserved in a transgenic mouse model of amyotrophic lateral sclerosis (SOD1 G93A ), and the mechanism of neurodegeneration in general are unknown. Hyperexcitability and calcium dysregulation have been proposed by others on the basis of data from juvenile mice that are, however, asymptomatic. No studies have been done with symptomatic mice following disease progression to the disease endstage. Here, we developed a new brainstem slice preparation for whole‐cell patch‐clamp recordings and single cell fura‐2 calcium imaging to study motoneurons in adult wild‐type and SOD1 G93A mice up to disease endstage. We analysed disease‐stage‐dependent electrophysiological properties and intracellular Ca 2+ handling of vulnerable hypoglossal motoneurons in comparison to resistant oculomotor neurons. Thereby, we identified a transient hyperexcitability in presymptomatic but not in endstage vulnerable motoneurons. Additionally, we revealed a remodelling of intracellular Ca 2+ clearance within vulnerable but not resistant motoneurons at disease endstage characterised by a reduction of uniporter‐dependent mitochondrial Ca 2+ uptake and enhanced Ca 2+ extrusion across the plasma membrane. Our study challenged the notion that hyperexcitability is a direct cause of neurodegeneration in SOD1 G93A mice, but molecularly identified a Ca 2+ clearance deficit in motoneurons and an adaptive Ca 2+ handling strategy that might be targeted by future therapeutic strategies.